ADAPTIVE INFORMATION TECHNOLOGY OF THE TROJAN’ DETECTION IN COMPUTER SYSTEMS - Savenko, Oleg; Lysenko, Sergiy (International Journal of Computing, 2011)
Adaptive information technology of computer systems Trojans diagnosing, which includes methods of diagnosing computer systems in monitor and scanner modes and allows improving reliability and efficiency, is developed. It is based on the behavioral model and the model of diagnosis. Computer system Trojan diagnosis software, which made it possible to detect the new Trojans with high reliability and efficiency, was developed.